Jogos entre o visível e o invisível na desconstrução das representações do real em Abbas Kiarostami - Assini, Tânia Cristina Kaminski Alves (2020)
The study reflects on contemporary filmic language aspects, in relation to the language hybridisation, storytelling dissolution, games between the visible and the invisible of the image and temporal displacements, to think about the limits of mise en scéne on the borders between the real and the fictional, as a focus for the deconstruction of representations of the "real" or truths and simulacrum. In regard to the mise en scéne artistic elements are apparent and that act in the deconstruction of representations of the real and in the sliding between the visible and the invisible. To what extent can the creative processes in Shirin and Certified Copy, by establishing relations with contemporary theories of art, literature and photography, moving away from the classical mise en scène, provokes reflections about the notions of representation and anti-representation in the cine? As methodology, this is comparative and analytical research, considering the study of the montage elements and mise en scène of films. In order to understand the artistic proposal of the films Shirin and Certified Copy, we sought theoretical support in the montage studies and mise en scène processes based on the reflections of Serguei M. Eisenstein (1974, 2002a, 2002b), Andre Bazin (1985, 1991), Jacques Aumont (1995, 2004,2006). To deal with cinema, hybridsm and heterogeneity we used the Mikhail Bakhtin (1993) end Denize Correa Araujo (2007) study. Considering the poetic and philosophical lines of force that act in those films in the compositional methods, we sought the contributions of Henry Bergson (1990), Andrei Tarkovski (2002), Walter Benjamin (1985), Gilles Deleuze (1990, 2006), Christian Jambet (2006), among others.